Dielectric Properties of Cryoprotective Media Based on DMSO and Glucose Supplemented with Cerium Dioxide - Mabana, Mishel A.; Skripnyk, Tamara V.; Chizhevsky, Victor V.; Goloyad, Mikhail A.; Gorobchenko, Olga A. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 163